Analysis of Rail Vehicle Axle Strength and Fatigue Crack Propagation Life - LI Rui-xia; ZHAO Li; QI Shuang-qiang; WANG Gui-jun (机车电传动)
Taking axle of GCY300II 12t-axle-load rail car as research object, according to locomotive axle strength standards, axle static and fatigue strength of the six different conditions with different axle load was calculated with finite element method. Based on the stress distribution and numerical value, static and fatigue strength of axle were analyzed, and weak parts of the axle was determined. Assuming the weakest parts of axle, and taking stress values of different axle load and different conditions as axle cracking-point stress spectrum, fatigue crack propagation life of axle was analyzed combined with theoretical calculation. The results showed that variable cross-section was weak part of axle, and the weakest part was edge of inside wheel seat.